2020
DOI: 10.1002/jcp.30103
|View full text |Cite
|
Sign up to set email alerts
|

IL‐1/IL‐1R signaling induced by all‐trans‐retinal contributes to complement alternative pathway activation in retinal pigment epithelium

Abstract: The underlying mechanisms of complement activation in Stargardt disease type 1 (STGD1) and age‐related macular degeneration (AMD) are not fully understood. Overaccumulation of all‐trans‐retinal (atRAL) has been proposed as the pathogenic factor in both diseases. By incubating retinal pigment epithelium (RPE) cells with atRAL, we showed that C5b‐9 membrane attack complexes (MACs) were generated mainly through complement alternative pathway. An increase in complement factor B (CFB) expression as well as downregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…To further investigate if the immune response in the Fmr1 KO is different than in wild types, we assessed the correlations between the expression of cytokines and the complement system target C3. The cytokines IL-6, IL-1β, and TNF-α have been previously shown to modulate C3 signaling [32,45]. In wild-type mice, we found a correlation between IL-6 and C3 at baseline, while, after LPS administration, C3 expression presented a positive correlation with the expression of IL-1β and TNF-α.…”
Section: Discussionsupporting
confidence: 46%
“…To further investigate if the immune response in the Fmr1 KO is different than in wild types, we assessed the correlations between the expression of cytokines and the complement system target C3. The cytokines IL-6, IL-1β, and TNF-α have been previously shown to modulate C3 signaling [32,45]. In wild-type mice, we found a correlation between IL-6 and C3 at baseline, while, after LPS administration, C3 expression presented a positive correlation with the expression of IL-1β and TNF-α.…”
Section: Discussionsupporting
confidence: 46%
“…We found that IL-1β could signi cantly promote the expression of CFH in FLSs and healthy controls-derived monocytes. IL-1/IL-1R signaling induced by all-trans-retinal contributes to complement alternative pathway activation in retinal pigment epithelium 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The complement system is widely expressed in central and peripheral nerves. Complement signaling has been associated with several neurological disorders, including traumatic brain injury, age-related macular degeneration, and Alzheimer's disease (63)(64)(65)(66)(67)(68). While most studies focus on the impact of the classical complement pathway, the role of alternative complement signaling in neuronal dysfunction and disorder remains to be explored.…”
Section: Discussionmentioning
confidence: 99%